PEMANFAATAN TEPUNG AMPAS KEDELAI PADA PEMBUATAN KUE TRADISIONAL KEMBANG GOYANG: Utilization Of Soybean Waste Flour in Making of The Traditional Snack Of Kembang Goyang - Shanti Pujilestari; Syahril Makosim; Ismi Asih (Fakultas Teknologi Pangan dan Agroindustri, Universitas Mataram, 2021)
ABSTRACT Kembang goyang snack is a traditional Indonesian food with a crunchy texture. The main ingredient for this snack is rice flour. Utilization of soybean waste flour formulated with rice flour in kembang goyang snack will increase the nutritional value however, it will decrease the crispness. The purpose of this study was to determine the effect of different formulations of rice flour and soybean waste flour (100:0, 90:10, 80:20, 70:30, and 60:40) on the quality of the kembang goyang snack. The quality of the cakes consists of physical quality (crisp), chemical (moisture content, ash content, protein content, fat content, carbohydrate content, crude fiber content), and organoleptic (color, aroma, taste, and texture). This study used an experimental method with a single factor Completely Randomized Design (CRD) with five levels. Each level consisted of 3 replications. The data will be analyzed by analysis of variance (ANOVA) and further test with Duncan’s test if the results of the ANOVA test are significant. The results showed that the different formulations of rice flour and soybean waste flour affected the physical, chemical, and organoleptic qualities (α=0.01). The more formulations of soybean waste flour used, the water, ash, protein, fat, crude fiber, and unpleasant aroma content will increase, while the crispness, carbohydrate content, color, taste, and texture will decrease. The acceptable formulations of rice flour and soybean waste flour in kembang goyang snack are 80:20, with 11.37 g/mm2 crispness, 2.51% water content, 1.02% ash, 8.43% protein, 24.23% fat, 63.81% carbohydrates, 3.60% crude fiber and 8.35% dietary fiber as well as an organoleptic quality which includes brownish yellow color, not strong soybean aroma, slightly sweet and savory taste, and crispness texture. The moisture content of the kembang goyang snack complies with Indonesian National Standard for rice crackers SNI 01-4307-1996. ABSTRAK Kembang goyang adalah kue tradisional Indonesia dengan tekstur renyah. Bahan utama kue kembang goyang adalah tepung beras. Pemanfaatan tepung ampas kedelai yang diformulasikan dengan tepung beras pada kue kembang goyang akan meningkatkan nilai gizi, tetapi akan menurunkan kerenyahannya. Tujuan dari penelitian ini untuk mengetahui pengaruh formulasi tepung beras dan tepung ampas kedelai yang berbeda (100:0, 90:10, 80:20, 70:30, dan 60:40) terhadap mutu kue kembang goyang. Mutu kue kembang goyang terdiri dari mutu fisik (kerenyahan), kimia (kadar air, kadar abu, kadar protein, kadar lemak, kadar karbohidrat, kadar serat kasar) dan organoleptik (warna, aroma, rasa dan tekstur). Penelitian ini menggunakan metode eksperimen dengan Rancangan Acak Lengkap (RAL) faktor tunggal dengan lima taraf. Masing-masing taraf terdiri dari 3 ulangan. Data akan dianalisa dengan analisis varian (ANAVA) dan uji lanjut dengan DMRT, bila hasil uji ANAVA signifikan. Hasil penelitian menyatakan bahwa formulasi tepung beras dan tepung ampas kedelai yang berbeda memengaruhi mutu fisik, kimia dan organoleptik (α=0.01). Semakin banyak formulasi tepung ampas kedelai yang digunakan maka kadar air, abu, protein, lemak, serat kasar, dan aroma langu akan semakin meningkat, sedangkan kerenyahan, kadar karbohidrat, warna, rasa, dan tekstur semakin menurun. Formulasi tepung beras dan tepung ampas kedelai pada kue kembang goyang yang masih dapat diterima adalah 80:20, dengan kerenyahan 11.37 g/mm2, kadar air 2.51%, abu 1.02%, protein 8.43%, lemak 24.23%, karbohidrat 63.81%, serat kasar 3.6% dan serat pangan 8.35% serta mutu organoleptik yang meliputi warna kuning kecoklatan, aroma langu kedelai tidak kuat, rasa agak manis dan gurih, serta tekstur renyah. Kadar air kue kembang goyang memenuhi Standar Nasional Indonesia kerupuk beras SNI 01-4307-1996.